2023
DOI: 10.1177/15459683231152816
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Lesion Volume and Injury to Motor Cortex Output Determines Extent of Contralesional Motor Cortex Reorganization

Abstract: Background After stroke, increases in contralesional primary motor cortex (M1CL) activity and excitability have been reported. In pre-clinical studies, M1CL reorganization is related to the extent of ipsilesional M1 (M1IL) injury, but this has yet to be tested clinically. Objectives We tested the hypothesis that the extent of damage to the ipsilesional M1 and/or its corticospinal tract (CST) determines the magnitude of M1CL reorganization and its relationship to affected hand function in humans recovering from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…This association is crucial in determining the extent of contralateral M1 reorganization. 21 It was reported that there was a reduction in the size and volume of the ipsilesional cortical hand motor representation, along with an anterior-medial shift of the contralesional hand motor representation within the contralesional primary motor cortex. 22 The combination with cTBS over the contralesional primary motor cortex and upper limb training promoted recovery of the upper limb, reduced disability and dependence, and led to earlier discharge from the rehabilitation center in patients within 3 weeks after stroke onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This association is crucial in determining the extent of contralateral M1 reorganization. 21 It was reported that there was a reduction in the size and volume of the ipsilesional cortical hand motor representation, along with an anterior-medial shift of the contralesional hand motor representation within the contralesional primary motor cortex. 22 The combination with cTBS over the contralesional primary motor cortex and upper limb training promoted recovery of the upper limb, reduced disability and dependence, and led to earlier discharge from the rehabilitation center in patients within 3 weeks after stroke onset.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study demonstrated that larger lesion volumes and increased severity in the corticospinal tract (CST), particularly in CST fibers originating from the lesioned primary motor cortex (M1), were associated with a more significant impairment of hand function. This association is crucial in determining the extent of contralateral M1 reorganization . It was reported that there was a reduction in the size and volume of the ipsilesional cortical hand motor representation, along with an anterior-medial shift of the contralesional hand motor representation within the contralesional primary motor cortex .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a unilateral large-sized lesion affecting most primary and premotor areas leads to initial paralysis in the contralateral arm. However, recruitment of the contra-lesional motor cortex (Cramer et al 1997, Ward et al 2003, Bestmann et al 2010, Rehme et al 2011, Zaaimi et al 2012, Murata et al 2015, Dodd et al 2017, McPherson et al 2018, Buetefisch et al 2023) leads to some degree of recovery of function via ipsilateral projections to the reticular formation, which then projects to the spinal cord via the reticulospinal tract (Illert et al 1981; see Bradnam et al 2012 for review). Because reticular projections to the spinal cord are mostly oligosynaptic via propriospinal neurons linking multiple muscles (Peterson et al 1975, Alstermark et al 2007), they create muscle synergies in the intact nervous system (Pierrot-Deseilligny 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have highlighted MEP status (MEP+ vs. MEP−) as a promising indicator of motor outcomes. 3 Additionally, researchers have developed a predictive recovery potential (PREP) algorithm, integrating motor scores, MEP status, and MRI measurements, exhibiting strong predictive abilities for stroke patients' motor outcomes. 4 However, in a recent study, researcher found that absence of MEP does not predict poor recovery in patients with severe stroke, 5 indicating that relying solely on MEP status may not comprehensively capture the multifaceted nature of poststroke motor function recovery.…”
Section: Introductionmentioning
confidence: 99%
“…A key method to assess functional integrity of CST involves using TMS to stimulate the primary motor cortex (M1) on the affected side and observing for the induction of motor evoked potentials (MEP). Studies have highlighted MEP status (MEP+ vs. MEP−) as a promising indicator of motor outcomes 3 . Additionally, researchers have developed a predictive recovery potential (PREP) algorithm, integrating motor scores, MEP status, and MRI measurements, exhibiting strong predictive abilities for stroke patients' motor outcomes 4 .…”
Section: Introductionmentioning
confidence: 99%